Slit-lamp Pars Plana Needle Hyaloidotomy-Zonulotomy-Iridotomy for the Treatment of Spontaneous Malignant Glaucoma. Issue 5 (May 2020) - Thomas, Merina; Boese, Erin A.; Lieu, Philip; Shah, Manjool
Abstract : An 88-year-old woman with a history of recent complicated pacemaker insertion presented with acute-onset malignant glaucoma recalcitrant to conservative medical therapy. Surgical intervention was discussed; however, given her complex cardiac history and recent postoperative state, the risk of anesthesia-related systemic adverse events was deemed unacceptably high. As such, a slit-lamp procedure was recommended to break the attack of malignant glaucoma. Here within, we report a novel technique of breaking an attack of malignant glaucoma by needling the anterior hyaloid face at the slit lamp. With this technique, a 25-G needle was entered through the pars plana and was advanced through the anterior hyaloid face, zonules, and peripheral iridotomy to create a unicameral eye and successfully break the malignant closure attack.